Evaluation of the Sinc Parametric Linear Combination Pulse in Digital Communication Systems - Soto-Gomez, J; Dehghan-Firoozabadi, A (Institute of Electrical and Electronics Engineers Inc., 2016)
Digital baseband communication systems are characterized by having a filter at the transmitter and receiver side to band limit the transmitted signals and diminish the effects to intersymbol interference (ISI). The impulse response of the sinc parametric linear combination pulse (SPLCP) is derived in the time domain, whereas its frequency response is also evaluated. The SPCLP is evaluated at the transmitter and receiver side by using different evaluation tools. Eye diagrams are presented to visually evaluate the susceptibility of the transmission system to ISI, and the maximum distortion is estimated as a quantitative measure of performance. The SPLCP outperforms other existing pulses in terms of bit error rate (BER), for various roll-off factors and symbol timing errors. © 2016 IEEE.